Effects of Supplementing Laying Hens with Purified Amino Acid Prepared from Animal Blood - Joshi, N.; Wandita, T. G.; Yang, S.; Park, H.; Hwang, S. G. (Tropical Animal Science Journal, 2019)
The objective of the experiment was to investigate the effects of supplementing laying hens with purified amino acids (PAA) derived from the blood of animal slaughter house on their egg production, egg quality, and immune response. The experiment was based on completely randomized design. A total of 144 Isa Brown laying hens (56-weeks old) were randomly allotted to 4 treatments with 4 pen replications (control, T1: 0.05%, T2: 0.1%, and T3: 0.5% PAA). Each pen housed nine laying hens. The laying hens were reared under a deep litter system. Once a week, a total of 12 eggs of each treatment were collected for egg quality analysis. At the end of the experiment, blood samples were collected for biochemical analysis and cytokines profiles using ELISA kit assays. Hen day egg production and hen house egg production increased significantly (P